Carbohydrate-based vaccines with a glycolipid adjuvant for breast cancer - Huang, Yen-Lin; Hung, Jung-Tung; Cheung, Sarah K. C.; Lee, Hsin-Yu; Chu, Kuo-Ching; Li, Shiou-Ting; Lin, Yu-Chen; Ren, Chien-Tai; Cheng, Ting-Jen R.; Hsu, Tsui-Ling; Yu, Alice L.; Wu, Chung-Yi; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Globo H (GH) is a hexasaccharide specifically overexpressed on a variety of cancer cells and therefore, a good candidate for cancer vaccine development. To identify the optimal carrier and adjuvant combination, we chemically synthesized and linked GH to a carrier protein, including keyhole limpet hemocyanion, diphtheria toxoid cross-reactive material (CRM) 197 (DT), tetanus toxoid, and BSA, and combined with an adjuvant, and it was administered to mice for the study of immune response. Glycan microarray analysis of the antiserum obtained indicated that the combination of GH-DT adjuvanted with the α-galactosylceramide C34 has the highest enhancement of anti-GH IgG. Compared with the phase III clinical trial vaccine, GH–keyhole limpet hemocyanion/QS21, the GH-DT/C34 vaccine elicited more IgG antibodies, which are more selective for GH and the GH-related epitopes, stage-specific embryonic antigen 3 (SSEA3) and SSEA4, all of which were specifically overexpressed on breast cancer cells and breast cancer stem cells with SSEA4 at the highest level (>90%). We, therefore, further developed SSEA4-DT/C34 as a vaccine candidate, and after immunization, it was found that the elicited antibodies are also IgG-dominant and very specific for SSEA4.